2011
DOI: 10.1590/s1516-18462011005000030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação para a língua Portuguesa e aplicação de protocolo de avaliação das disartrias de origem central em pacientes com Doença de Parkinson

Abstract: RESUMOObjetivo: traduzir e adaptar protocolo desenvolvido por pesquisadores alemães, adequando-o às características fonéticas e linguísticas do português falado no Brasil. Caracterizar os componentes de fala mais alterados na população com doença de Parkinson, comparando-os com grupo de sujeitos normais na mesma faixa etária. Método: realizou-se a tradução e adaptação do protocolo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 12 publications
1
18
0
6
Order By: Relevance
“…These findings corroborate with other studies 10,17,22 that found lower amplitude of NT melodic variation in individuals with PD, giving speech a monotonous quality. The same stu dies show a lower rate of change of NT melodic variation in PD off compared with CG regarding the emission of short de clarative utterances.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings corroborate with other studies 10,17,22 that found lower amplitude of NT melodic variation in individuals with PD, giving speech a monotonous quality. The same stu dies show a lower rate of change of NT melodic variation in PD off compared with CG regarding the emission of short de clarative utterances.…”
Section: Discussionsupporting
confidence: 93%
“…Durations were significantly higher for individuals with PD. This can also be explained by bradykinesia and difficulty in controlling air flow 22,25,26 . Comparing CG off with PD off, we found lower average intensity of utterance in males.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of dysarthria was performed according to the "Dysarthria Evaluation Report", adapting to the phonetic and linguistic characteristics of the Brazilian Portuguese, and formulated with the most altered components of the speech (12) . The data collected were recorded through audio and video, using an external sound board (by M-audio), microphone (SM-58), PRAAT (Programa de Análise Acústica) software, and Sony Cyber-shot camera of 7.2 megapixels.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are few standardized evaluation instruments aimed at the adult population (2,3) , especially instruments with linguistic and psychometric criteria, and that allow the achievement of quantitative results.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the adult population, the main instruments for the perceptual speech evaluations are: the Sentence Intelligence Test (SIT) (4) , the Protocol for the Evaluation of Dysarthria (3) , the Protocol for the Evaluation of Speech Intelligibility in Dysarthria -PAIF (5,6) , and the Verbal and Nonverbal Apraxia Protocol (7) . In addition to perceptual speech evaluations, there are currently quantitative instrumental evaluations, such as speech ultrasonography and nasometry, among others, that allow the clinician to identify each level of speech production and to obtain reliable parameters regarding the levels involved in speech production (8) .…”
Section: Introductionmentioning
confidence: 99%